A Review of Behavioral Interventions for Anxiety‐Related Behaviors in Lower‐Functioning Individuals with Autism. (11th February 2016) - Rosen, Tamara E.; Connell, James E.; Kerns, Connor M.
Abstract : Anxiety is highly prevalent in persons with autism and affects individuals with higher‐functioning autism (HFA) and lower‐functioning autism (LFA). Although there is emerging support for the efficacy of cognitive‐behavioral therapy (CBT) in treating anxiety in autism, these findings are largely based on HFA samples. Moreover, CBT may be inappropriate for individuals with LFA who may struggle to grasp the cognitive components of the therapy because of their more limited verbal abilities. Behavior analytic interventions may be better suited to treat anxiety in this population; however, the quantity and quality of the extant literature have yet to be reviewed. Toward this end, the extant behavioral intervention literature was reviewed. Seven studies met the inclusion criteria and were evaluated against quality indicators for within‐subject design research. Next, the efficacy of each treatment component was assessed using established criteria for defining empirically supported therapies. Results revealed behavioral interventions to be efficacious, with desensitization and reinforcement emerging as efficacious treatment components, while prompting, modeling, and antianxiety stimuli were established as possibly efficacious. However, given that some of the quality indicators were not met, these results should be interpreted with some caution. Additional research is needed to form a more conclusive evidence base for the treatment of anxiety in individuals with LFA. Copyright © 2016 John Wiley & Sons, Ltd.